2018
DOI: 10.11591/ijere.v7i3.13776
|View full text |Cite
|
Sign up to set email alerts
|

Logo Counseling for Low Spiritual Self-Esteem Among College Students

Abstract: The purpose of this research was to examine logo counseling model in improving low spiritual self-esteem problem for college students. This research used descriptive method and quasi-experiment method with a non-equivalent pre-test-post-test control group design. The results then analyzed from the statistical significance and the practical significance. The result showed that logo counseling model could improve low spiritual self-esteem among college students, indicated by statistical significance of t<sub&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Berkel & Hinshaw, 2014; Titi, Budi, & Novy Helena, 2018;Vos, Craig, & Cooper, 2014). Effectiveness studies for logotherapy have also indicated a reduction in symptoms and an improvement in self-efficacy and goal setting (e.g., Engel & Yusuf, 2013;Faramarzi & Bavali, 2017;Hajiazizi, Bahmani, Mahdi & Tavakoli, 2017;Hamidi, Manshee, & Fard, 2013;Joshi, Marszalek, Berkel, & Hinshaw, 2014;Montrell, 2020;Robatmili, et al, 2015;Thompson, 2016;Vos, Craig & Cooper, 2014). Research is also providing validation for the logotherapeutic model (Joshi et al, 2014) and the potential practical application of logotherapy into the health profession (Mortell, 2020).…”
Section: /12mentioning
confidence: 99%
“…Berkel & Hinshaw, 2014; Titi, Budi, & Novy Helena, 2018;Vos, Craig, & Cooper, 2014). Effectiveness studies for logotherapy have also indicated a reduction in symptoms and an improvement in self-efficacy and goal setting (e.g., Engel & Yusuf, 2013;Faramarzi & Bavali, 2017;Hajiazizi, Bahmani, Mahdi & Tavakoli, 2017;Hamidi, Manshee, & Fard, 2013;Joshi, Marszalek, Berkel, & Hinshaw, 2014;Montrell, 2020;Robatmili, et al, 2015;Thompson, 2016;Vos, Craig & Cooper, 2014). Research is also providing validation for the logotherapeutic model (Joshi et al, 2014) and the potential practical application of logotherapy into the health profession (Mortell, 2020).…”
Section: /12mentioning
confidence: 99%
“…Logo counseling, a logotherapy modification, was developed to overcome the causative factors of low self-esteem as well as to discover meaning and purpose in the life of the students [1]. In addition, to overcome physical and psychological issues, the innovative model of logo counseling website was successfully designed with objectives and implemented with good responses from students [2].…”
Section: Introductionmentioning
confidence: 99%